Descriptors for farmers' knowledge of plants - Bioversity International (2009)
This list of descriptors has been developed by Bioversity International to provide a standard format for the gathering, storage, retrieval and exchange of farmers’ knowledge of plants. The list aims to capture key characteristics, uses and values of cultivated and wild plants as described by farmers and other people in farming communities. Many of these descriptors are not included in conventional descriptor lists. Wild and weedy plants are also covered by this list since they often play a significant role in farming communities, being useful from a socio-economic and ecological standpoint.